Response of rapeseed to sulphur application under two soil series of Meghalaya - SAIBORNE, IAN BORNEY; LENKA, N. K.; SINGH, A. K. (Journal of Soil and Water Conservation, 2021)
Intensive cultivation on hill slopes is a major cause of soil degradation and depletion of soil fertility in hilly regions. To assess the status of an increasingly important plant nutrient, sulphur (S), an experiment was conducted with soils of two soil series, Nongpoh and Umsoing (Umsning), collected from different land uses such as maize-millets, ginger-turmeric, citrus orchard, low land paddy and tea plantation. The study was done with rapeseed as test crop in the rabi season of 2008-09. The objective of the experiment was to study the effect of S application on dry matter yield and uptake of sulphur in different soils of Meghalaya. Four levels of S, i.e. 0 (control), 20, 40 and 60 mg S kg-1 soil were taken for the study. The data showed that dry matter yield increase was significant up to the level of 40 mg kg-1 in five out of the eight soils studied and uptake of S was significant in three soils of Nongpoh series and two soils of Umsoing series. Average response to application of S as compared to control were 92, 132 and 162% for 20, 40 and 60 mg S kg-1 application levels.